EFFECTIVENESS AND IMPACT ANALYSIS INDEPENDENT CURRICULUM ON STUDENT LEARNING OUTCOMES - Hanif Irawan Saputra; Hastin Suryaningsih; Prima Khoirunisa; Mahilda Dea Komalasari (Sindoro: Cendikia Pendidikan, 2025)
Effectiveness in learning is very important in the world of education. As a teacher, you must also have the ability to actively participate in the learning process, be creative and innovative, and have the ability to act as a driver of change in their educational environment. However, this will definitely have an impact in the process. This research uses a literature study or literature study which discusses the effectiveness of the independent curriculum and the impacts that occur. Literature contained in articles, journals and other sources can be found on the internet. The literature study method is used by searching and collecting relevant sources, filtering the sources to be studied, and then making conclusions about various important things in written form.